2021
DOI: 10.5114/ada.2021.107933
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of dermal equivalent of hypothalamuspituitary- adrenal axis in mastocytosis

Abstract: Introduction Mastocytosis is a rare disease characterized by abnormal growth and accumulation of tissue mast cells (MC) in one or more organ systems and is classified as being either cutaneous mastocytosis (CM) or systemic mastocytosis (SM). In the pioneer studies of Slominski's group, a fully functional hypothalamic-pituitary-adrenal axis equivalent has been discovered in various tissues, including skin. Aim In the present study we investigated potential involvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In turn, IL-6 secreted by mast cells can induce CRH secretion by activating the HPA axis [ 45 ]. Interestingly, a recent study has shown deregulation of the skin equivalent of the HPA axis in cutaneous mastocytosis (neoplastic proliferation of mast cells in the skin) [ 101 ], which highlights the underlying importance of mast cells in dermal homeostasis.…”
Section: The Hpa Axis Links Psoriasis and Depressionmentioning
confidence: 99%
“…In turn, IL-6 secreted by mast cells can induce CRH secretion by activating the HPA axis [ 45 ]. Interestingly, a recent study has shown deregulation of the skin equivalent of the HPA axis in cutaneous mastocytosis (neoplastic proliferation of mast cells in the skin) [ 101 ], which highlights the underlying importance of mast cells in dermal homeostasis.…”
Section: The Hpa Axis Links Psoriasis and Depressionmentioning
confidence: 99%
“…In a study by Antoniewicz et al [ 92 ], significantly elevated serum concentrations of adrenocorticotropic hormone (ACTH) were reported in patients with mastocytosis when compared to the control group. These findings support the idea of an altered skin HPA (sHPA) axis in patients with mastocytosis.…”
Section: Pathogenetic Link Between Mastocytosis and Skin Cancermentioning
confidence: 99%
“…The corticotropin-releasing hormone (CRH) is overexpressed in areas of inflammation, as well as in peripheral tissues including the skin [ 30 ], thus its dysregulation is an important factor in psoriasis pathogenesis [ 31 , 32 , 33 , 34 , 35 ]. Correspondingly, aberrant CRH-receptor 1 is linked to psoriasis [ 28 , 36 , 37 , 38 ]. The increase of CRH in psoriasis can be accompanied by the up-regulation of proopiomelanocortin (POMC) [ 39 ], melanin-concentrating hormone receptor (MCHR1), and melanocortin receptors 2, 3 and 4 [ 40 ].…”
Section: Psoriasis and The Local Endocrine Regulatorsmentioning
confidence: 99%